Beyond Iraq the future of world order - Acharya, Amitav; Katsumata, Hiro, 1970- (Series on the Iraq War and its consequences ;, 2011)
How does the Iraq War affect the future world order? And what kinds of problems has this war brought about, and what is needed to remedy these problems, so as to reconstruct an order in Iraq and beyond? This volume is a collection of essays exploring these issues.